STANDARISASI SISTEM TULISAN JAWI DI DUNIA MELAYU: Sebuah Upaya Mencari Standar Penulisan yang Baku Berdasarkan Aspek Fonetis - Masyhur Dungcik; Bety Bety (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract:Since his arrival in the Malay Archipelago, Islam brings together Arabic or Jawi as a system of writing systems in the Malay language. This writing system using Arabic script known as Jawi. The pronouncing of the term Jawi for letters is closely related to the designation of Jawi used by the Arabs, especially in Mecca against the Malay and Indonesian nation to this day. The term Jawi is an adjective that means people coming from Java or Java Island. Arab writers in the classical era, including Ibn Battuta in his book Al-Rihlah called the island of Sumatra as Al-Jawah. Therefore, the Arabs concluded Malays and Javanese as a nation of Jawi and Malay writing that uses the Arabic alphabet was called by writing letters or Jawi.      Currently, there are at least three terms to refer to this article. Besides known as Jawi writing in Malaysia and Brunei, this paper is also known by the Arabic term Malay in Palembang and Sumatra region. While on the island of Java, called the letter Pegon or Arabic Pegon. Even for Pegon letter only applies to Arabic/Jawi or the Java language, but this phenomenon remains that there is no uniformity of the term/name for this article. Uniformity of terms may be obtained if there is a standard of Jawi writing itself. Because in reality there are a variety of Jawi writings. Methods which are true and can be used as a handle, could not be ascertained unless acquired scientific standards for spelling and writing system. Speaking of writing/script then it means talking about the sound (letter). Sounds called phonemes in terms of linguistic/Linguistics. Science that examines the phoneme is called Science or Phonology Phonetics.      This paper attempts to analyze the Jawi writing from the perspective of Phonetic Sciences mainly Arabic Phonetics (Ilm al-Ashwat) because it is recognized or not, basically the script used in the Jawi script is Arabic with various adjustments (additional letters) to represent the letters, which are not contained in the Arabic script. This study aims to find the right principle for Jawi based on study of Phonetic Sciences, in the hope of finding uniformity principle on Jawi writing. Methods which are more in line with principle of Phonetics (Ilm al-Ashwat), principle that might be appropriate to serve as a standard of writing Jawi. As a result, we may be able to find the term / permanent name and appropriate for the Jawi script.Keywords: Writing of Jawi, Malayan, and Phonetics